Low NAD+ Levels Are Associated With a Decline of Spermatogenesis in Transgenic ANDY and Aging Mice - Mirella L. Meyer-Ficca; Mirella L. Meyer-Ficca; Alexie E. Zwerdling; Corey A. Swanson; Abby G. Tucker; Sierra A. Lopez; Sierra A. Lopez; Miles K. Wandersee; Miles K. Wandersee; Gina M. Warner; Gina M. Warner; Katie L. Thompson; et al. (Frontiers in Endocrinology, 2022)
Advanced paternal age has increasingly been recognized as a risk factor for male fertility and progeny health. While underlying causes are not well understood, aging is associated with a continuous decline of blood and tissue NAD+ levels, as well as a decline of testicular functions. The important basic question to what extent ageing-related NAD+ decline is functionally linked to decreased male fertility has been difficult to address due to the pleiotropic effects of aging, and the lack of a suitable animal model in which NAD+ levels can be lowered experimentally in chronologically young adult males. We therefore developed a transgenic mouse model of acquired niacin dependency (ANDY), in which NAD+ levels can be experimentally lowered using a niacin-deficient, chemically defined diet. Using ANDY mice, this report demonstrates for the first time that decreasing body-wide NAD+ levels in young adult mice, including in the testes, to levels that match or exceed the natural NAD+ decline observed in old mice, results in the disruption of spermatogenesis with small testis sizes and reduced sperm counts. ANDY mice are dependent on dietary vitamin B3 (niacin) for NAD+ synthesis, similar to humans. NAD+-deficiency the animals develop on a niacin-free diet is reversed by niacin supplementation. Providing niacin to NAD+-depleted ANDY mice fully rescued spermatogenesis and restored normal testis weight in the animals. The results suggest that NAD+ is important for proper spermatogenesis and that its declining levels during aging are functionally linked to declining spermatogenesis and male fertility. Functions of NAD+ in retinoic acid synthesis, which is an essential testicular signaling pathway regulating spermatogonial proliferation and differentiation, may offer a plausible mechanism for the hypospermatogenesis observed in NAD+-deficient mice.